The Integration of Technology-assisted Assessment in esl (English as a second Language) Instruction (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores the incorporation of technology-assisted evaluation in English as a Second Language (ESL) teaching and its influence on educational achievements. The study investigates the effectiveness of using several technology tools, such as online platforms, adaptive software, and multimedia resources, to evaluate the language ability of ESL learners. Through the utilization of these tools, instructors strive to deliver interactive, captivating, and customized assessments that provide significant insights into learners' advancement and areas requiring enhancement. The study highlights the significance of accuracy in the design and execution of assessments to guarantee their validity and reliability. The text examines the role of technology in enhancing the gathering and examination of assessment data, empowering educators to make well-informed choices to improve instructional methods and to cater to the unique needs of each student. Moreover, the study explores the capacity of technology-supported evaluation to tackle issues encountered in conventional assessment approaches, such as the ability to handle large-scale assessments and ensure impartiality. Additionally, it emphasizes the importance of addressing implementation factors, such as guaranteeing availability of devices and dependable internet connectivity. In summary, this article argues in favour of incorporating technology-assisted assessment into ESL training to improve learning outcomes and promote better language proficiency among learners.